INSTITUTIONAL SUPPORT FOR FRESHWATER AQUACULTURE DEVELOPMENT-A STUDY OF MIRZAPUR DISTRICT OF UTTAR PRADESH, INDIA - Pandey, S. K.; Dewan, Ritu (Journal of Indian Fisheries Association, 2008)
The aquaculture sector has been playing an increasingly dominating role in Indian fisheries scenario since the last two and half decades. Introduction of induced breeding and composite fish culture (CFC) technologies has revolutionised the freshwater aquaculture sector in India. Institutional support has been one of the most crucial aspects in all fisheries development programmes, more so in the Indian context where most of fish farmers are socially and economically weak. The innovation of CFC technology in freshwater aquaculture sector in the early seventies generated the need for adequate and effective institutional support to farmers. Under the freshwater aquaculture development programme, the Fish Farmers Development Agencies (FFDA} have been established at district level to provide technical and extension support to the farming community besides arranging ponds on lease and supply of seeds. In addition to above, FFDAs are also expected to arrange loans from banks and provide subsidies. Thus, FFDAs are meant to provide institutional support to fish farming community in the country. In view of theabove, an effort was made to study the adequacy and effectiveness of institutional support provided by the FFDA, Mirza pur for the development of aquaculture in Mirzapur district of Uttar Pradesh {U.P.), India. Study reveals that leasing of ponds for fish farming has been favourable toeconomically weaker sections of societies while bank loan accessibility is more for those having relatively higher economic status. Though the FFDA, Mirzapur performed well in providing training to potential fish farmers and creating awareness about fish farming, its effectivenesscould not be equally seen in seed supply. Key words: Freshwater aquaculture, FFDA, lease, Bank loan and subsidy, Training, Seed supply.